Espaços não formais de ensino: Ensino de química em uma estação de tratamento de água - Sega, Daniel Luiz [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
In the educational system, it is common for science teaching to be worked out of context from everyday practices, which makes it more difficult to understand scientific knowledge. According to the National Curriculum Parameters for High School, science teaching is the duty to assist in the holistic education of students, not only scientific, but also in the construction of ethical values and citizenship. This work was carried out within the scope of the Licentiate Degree in Chemistry with the proposal of an educational practice for the teaching of Chemistry to be implemented in the 2nd year of high school, serving as support for teachers who wish to use the non-formal space and as an important addition content developed within the classroom. Non-formal education is an important tool to complement formal education, as this alone cannot meet all social demands. The activities in the non-formal space were planned and organized with their own dynamics, in which it is divided into 3 important stages that include the perspective of teaching CTSA (Science, Technology, Society and Environment) using a field class as an instrument to facilitate the learning Chemistry. The visit to the Water Treatment Plant is justified by the social importance of learning through the appropriation of the contents of the methods and concepts developed during the water purification process for human consumption and the possibility of contextualization between the contents developed in the classroom and the daily lives of students, unfolding from the scientific, technological, social and environmental points of view.

No sistema educacional é comum que o ensino de ciências seja trabalhado de forma descontextualizada das práticas do dia a dia, o que torna mais difícil a compreensão do conhecimento científico. Segundo os Parâmetros Curriculares Nacionais para o Ensino Médio, o ensino de ciências tem o dever de auxiliar na formação holística dos estudantes, não somente científica, mas também na construção valores éticos e de cidadania. Este trabalho foi realizado no âmbito do curso de Licenciatura em Química tendo como proposta uma prática educacional para o ensino de Química a ser implementada no 2º ano do ensino médio, servindo como suporte aos professores que desejarem utilizar o espaço não formal e como um importante acréscimo aos conteúdos desenvolvidos dentro da sala de aula. A educação não formal é uma importante ferramenta para complementar a educação formal, já que esta sozinha não tem possibilidade de atender a todas as demandas sociais. As atividades no espaço não formal foram planejadas e organizadas com uma dinâmica própria, na qual divide-se em em 3 etapas importantes que contemplam a perspectiva do ensino CTSA (Ciência, Tecnologia, Sociedade e Meio Ambiente) utilizando a aula de campo como instrumento facilitador da aprendizagem de Química. A visita à Estação de Tratamento de Água é justificada pela importância social do aprendizado por meio da apropriação dos conteúdos dos métodos e conceitos desenvolvidos durante o processo de purificação de água para o consumo humano e da possibilidade de contextualização entre os conteúdos desenvolvidos em sala de aula e o cotidiano dos alunos, desdobrando-se pelos pontos de vista científicos, tecnológicos, sociais e ambientais.
Non-Formal teaching spaces: Teaching chemistry at a water treatment plant
Keywords: Educational system; Scientific knowledge; Science teaching; Non-formal space; Sistema educacional; Conhecimento científico; Ensino de ciências; Educação extra-escolar; CTSA